2014
DOI: 10.1002/2014ms000339
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol effects on cirrus through ice nucleation in the Community Atmosphere Model CAM5 with a statistical cirrus scheme

Abstract: A statistical cirrus scheme that tracks ice saturation ratio in the clear-sky and cloudy portion of a grid box separately has been implemented into the Community Atmosphere Model CAM5 to provide a consistent treatment of ice nucleation and cloud formation. Simulated ice supersaturation and ice crystal number concentrations strongly depend on the number concentrations of heterogeneous ice nuclei (IN), subgrid temperature formulas, and the number concentration of sulfate particles participating in homogeneous fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
36
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 97 publications
(223 reference statements)
9
36
0
Order By: Relevance
“…The increased precipitation rate can be understood as a response to a cooler atmosphere overlaying warm and unchanged SSTs, destabilizing the atmospheric column. Another recent study of aerosol effects on cirrus clouds reported a similar short-term precipitation response, and found it to be closely related to the changes in atmospheric absorption of longwave radiation associated with cirrus clouds [40]. Such opposing short-term and long-term global precipitation responses have previously been reported for other forcing agents, e.g.…”
Section: Resultssupporting
confidence: 59%
“…The increased precipitation rate can be understood as a response to a cooler atmosphere overlaying warm and unchanged SSTs, destabilizing the atmospheric column. Another recent study of aerosol effects on cirrus clouds reported a similar short-term precipitation response, and found it to be closely related to the changes in atmospheric absorption of longwave radiation associated with cirrus clouds [40]. Such opposing short-term and long-term global precipitation responses have previously been reported for other forcing agents, e.g.…”
Section: Resultssupporting
confidence: 59%
“…The comparison between DH400 and DH300 indicates that even with only a few percent (i.e., 4.17%) of cirrus clouds formed from the homogeneous nucleation in DH400, homogeneous nucleation can have strong impacts on LWCF (by 4.44 W m −2 ) and shortwave cloud forcing (SWCF) (by −2.99 W m −2 ). The reduction of Fre hom results in a higher convective precipitation rate (PRECC), because the reduction in CDNI leads to decreasing of atmospheric stability and strengthening of deep convection [ Wang et al , ].…”
Section: Resultsmentioning
confidence: 99%
“…We note that both the modeling and observations of cirrus clouds; ice crystal numbers; and, in particular, the balance between homogeneous and heterogeneous ice nucleation are uncertain. Different authors have used different representations of updraft velocities which lead to differences in the fraction of homogeneous and heterogeneous ice nucleation [Wang and Penner, 2010;Gettelman et al, 2012;Wang et al, 2014;Shi et al, 2015]. It is possible to use the IMPACT aerosol concentrations and reproduce the ice number concentrations of Krämer et al [2009] if updraft velocities during ice nucleation events are based on the mesoscale temperature variations measured by Gary [2006Gary [ , 2008.…”
Section: Discussionmentioning
confidence: 99%